AOHDR 2017
DOI: 10.21276/aohdr.1762
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Prospective Study of Three different Bone Plating Methods for treatment of Mandibular Symphysis and Parasymphysis Fractures

Abstract: Background: Recently, various modifications in placing miniplates for direct fixation of the mandibular fracture are gaining popularity. The modifications have various advantages like more rigidity, less foreign material, less time in application, etc. Thus the purpose of this prospective study was to evaluate outcomes for three bone plating techniques used in the treatment of mandibular symphysis/ parasymphysis fractures. Material and Methods:A prospective study was conducted on 45 patients with mandibular sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Duration of surgery is minimal while the surgeons used 3D plates compared to conventional plates. Al-Moraissi and Ellis (2014); Shapoo et al (2017) also reported that the operative time is shorter while they used 3D plates. However in angle region placement of 3-D plates required extra time as reported by Feledy et al (2004); Sadhwani and Anchlia (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Duration of surgery is minimal while the surgeons used 3D plates compared to conventional plates. Al-Moraissi and Ellis (2014); Shapoo et al (2017) also reported that the operative time is shorter while they used 3D plates. However in angle region placement of 3-D plates required extra time as reported by Feledy et al (2004); Sadhwani and Anchlia (2013).…”
Section: Discussionmentioning
confidence: 99%